Clear Cell Carcinoma Arising in an Abdominal Wall Cesarean Section Scar: A Case Report With Description of Pathological and Molecular Features - Colarossi, Cristina; Picardo, Maria Carolina; Colarossi, Lorenzo; Deiana, Enrica; D'Agata, Costanza; Fichera, Corrado; Aiello, Eleonora; Giannone, Giorgio; Memeo, Lorenzo (Frontiers in Surgery, 2021)
Clear cell carcinoma is a clinically and biologically distinct type of carcinoma predominantly encountered in the ovary and endometrium. In the ovary, it is frequently associated with endometriosis, which is a well-known risk factor. Endometriosis has often been described in the abdominal wall of women who had a cesarean section; however, malignant transformation is a very rare event, occurring in < 1% of cases. The authors report a case involving a 52-year-old woman with an abdominal wall nodule at a cesarean section scar. Radiology revealed a mass, measuring 8 cm in size, in the abdominal wall suggestive of a soft tissue tumor. After resection, histology revealed the presence of clear, eosinophilic, and hobnail cells, which, together with immunohistochemical and molecular findings, enabled the diagnosis of clear cell carcinoma of the abdominal wall. The present report describes the clinical, radiological, pathological, and molecular features of an unusual abdominal lesion that represents a rare but challenging diagnosis.